Konsep Kepemimpinan Pendidikan Menurut Ibn Khaldun: Relevansi Bagi Pengembangan Manajemen Lembaga Pendidikan Islam - Sapri Sapri; Tamimi Mujahid; Rizqi Almajid; Muliana Putri; Adinda Rahma Rangkuti; Irfan Irfan; Abdi Syahputra (CV. PUSDIKRA MITRA JAYA, 2025)
This study aims to analyze the concept of educational leadership according to Ibn Khaldun and explore its relevance to the development of contemporary Islamic educational institution management. This study uses a qualitative method with a library research approach, through a review of Ibn Khaldun's al-Muqaddimah and the latest scientific literature from 2019–2025 related to Islamic education management, transformative leadership, and spiritual values in education. The results show that Ibn Khaldun places leadership as a major factor in the formation of civilization ('umran) and emphasizes that education is the main means of shaping civilized human beings. This study concludes that the application of Ibn Khaldun's leadership values can strengthen Islamic education management towards an adaptive, ethical, and sustainable system. The practical implication is that Islamic educational institutions need to develop a value-based management system and a collaborative organizational culture to face the challenges of the digital era without losing their spiritual identity.